2005
DOI: 10.1016/j.geomorph.2005.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Modelling differential catchment response to environmental change

Abstract: Lewin, John, Coulthard, T.J., Macklin, M.G., (2005) 'Modelling differential catchment response to environmental change', Geomorphology 69(1-4) pp.222-241 RAE2008The CAESAR (Cellular Automaton Evolutionary Slope And River) model is used to demonstrate significant differences in coarse sediment transfer and alluviation in medium sized catchments when responding to identical Holocene environmental changes. Simulations for four U.K. basins (the Rivers Swale, Ure, Nidd and Wharfe) shows that catchment response, dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(136 citation statements)
references
References 32 publications
4
131
0
Order By: Relevance
“…The cross-section surveys suggested that, over the period December 2001 to March 2004, the upper part of the study reach was aggradational, with a reach-and width-averaged mean rise in bed levels of 0·22 ± 0·021 m, and this fits with much longer timescale simulations of this reach which also suggest aggradation (Coulthard et al, 2005). (Figure 2).…”
Section: Resultsmentioning
confidence: 54%
“…The cross-section surveys suggested that, over the period December 2001 to March 2004, the upper part of the study reach was aggradational, with a reach-and width-averaged mean rise in bed levels of 0·22 ± 0·021 m, and this fits with much longer timescale simulations of this reach which also suggest aggradation (Coulthard et al, 2005). (Figure 2).…”
Section: Resultsmentioning
confidence: 54%
“…Terraces have formed in all global regions and are commonly studied to understand how rivers have responded to the combined effects of changes in external controls including climate, tectonics, and sea level (Merritts et al, 1994;Macklin et al, 2002;Bridgland and Westaway, 2008) and in internal controls, such as catchment morphology (Coulthard et al, 2005) and reach-specific conditions (Houben, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As stated in the model description, CAESAR has successfully simulated landscape evolution in a range of environments Macklin, 2001, 2003;Coulthard et al, 2012a;Hancock et al, 2011;Welsh et al, 2009), but it is important to question whether the non-linear response of the model is simply a model by-product or a representation of actual basin dynamics? CAESAR has a long history of modelling the non-linear reaction of catchments from 1998 through to 2010 Coulthard et al, 1998Coulthard et al, , 2005Van De Wiel and Coulthard, 2010) and given that similar non-linear dynamics have been well documented in fluvial systems (Cudden and Hoey, 2003;Gomez and Phillips, 1999;Hooke, 2003;Stølum, 1998), we consider the simulation of non-linear sediment dynamics in CAESAR genuine. In addition, CAESAR is certainly not the only model to show non-linear sediment responses.…”
Section: Discussionmentioning
confidence: 99%
“…Their simulations showed that changes in discharge input and sediment storage (reflected in increased valley floor gradients) led to spikes in sediment associated with increased water inputs. Coulthard et al (2005) calculated individual sediment budgets for reaches of a medium sized drainage basin from basin simulations carried out over a 9000 yr period. Their research showed that during wetter periods (increased rainfall magnitudes) there was a dramatic increase in sediment yields and this was largely sourced from the lower, valley floor sections of the catchment.…”
Section: Introductionmentioning
confidence: 99%